COUNSELING AND TRAINING IN MANUFACTURING COCOA BRICKETS FOR ECONOMIC EMPOWERMENT OF THE JONG DOBO FARMERS GROUP IN SIKKA DISTRICT - Gabriel Otan Apelabi; Yosep Darius Purnama Rangga; Agustinus J.P. Ana Saga; Yasintha Bolly, Yovita; Karolina Karmila; Kapistrano Herfosius Dewa (Fakultas Pertanian, 2024)
The partner in this PKM activity is the Jong Dobo Group in Ian Tena Village, Kewapante District, Sikka Regency. The results of a survey conducted by the PKM team found problems faced by partners in conducting cocoa farming, namely the abundance of cocoa shell waste due to an increase in cocoa production. The aim of this service activity is to increase farmers' knowledge in utilizing cocoa shells as an alternative fuel with economic value. Apart from increasing farmers' knowledge, this activity is also targeted at increasing farmers' skills in making cocoa shell briquettes. The method used in carrying out this service activity is demonstration method counseling (Demcar). The application of this method is through counseling and training. From the counseling and training that has been carried out, it was obtained that farmers' knowledge increased by 92.2% and skills by 83.2%. The follow-up plan for the service activities that have been carried out is that assistance is also needed for the analysis of the briquette making farming business.